Job Vacancies in the United States: 1923 to 1994 - Zagorsky, Jay L. (The Review of Economics and Statistics, 1998)
Empirical investigations of the U.S. macroeconomy often examine only the post-World War II period because very few key data series exist for earlier years. However, this brief time period misses major economic shocks like the Great Depression and World War II. Using a previously unknown data set, this paper solves part of the problem by creating a long-run job vacancy series from 1923 to 1994 based on help-wanted advertising data. Analysis suggests that the series is consistent and has no significant biases.